Porphyrins as Colorimetric and Photometric Biosensors in Modern Bioanalytical Systems - Senge, Mathias (Wiley, 2020)
Advances in porphyrin chemistry have provided novel materials and exciting technologies for bioanalysis such as colorimetric sensor array (CSA), photo-electrochemical (PEC) biosensing, and nanocomposites as peroxidase mimetics for glucose detection. This review highlights selected recent advances in the construction of supramolecular assemblies based on the porphyrin macrocycle that provide recognition of various biologically important entities through the unique porphyrin properties associated with colorimetry, spectrophotometry, and photo-electrochemistry. Keywords:
Keywords: Biorecognition; Biosensing; Colorimetry; Detection; Porphyrin